Testosterone regulation of cyclin E kinase: A key factor in determining gender differences in hepatocarcinogenesis. Issue 6 (June 2016) - Pok, Sharon; Barn, Vanessa A; Wong, Heng Jian; Blackburn, Anneke C; Board, Philip; Farrell, Geoffrey C; Teoh, Narci C
Abstract: Background and Aim: While gender differences in hepatocellular carcinoma (HCC) are profound, the mechanism is unclear. Using castration and hormone replacement strategies, we tested whether these gender differences are attributable to testosterone or estradiol/progesterone effects on cell cycle regulators and p53. Methods: We studied dysplastic liver and HCCs in intact and castrated diethylnitrosamine‐injected C57BL/6J male and female mice, with or without hormonal replacement. Effects of sex steroids on proliferation and survival of primary hepatocytes and primary HCC cells were also characterized. Results: Diethylnitrosamine‐injected female mice displayed fewer dysplastic foci and slower onset of HCC than male mice, with smaller/more differentiated tumors and fewer metastases. Castration of diethylnitrosamine‐injected male mice reduced cyclin E kinase and augmented hepatocyte apoptosis compared with intact male mice; estradiol/progesterone enhanced these effects. In intact female mice, cyclin E kinase activity was less than in males; testosterone administered to ovariectomized female mice upregulated cyclin E, increased cyclin E kinase, and accelerated hepatocarcinogenesis. In vitro, testosterone increased expression of cell cycle regulators (cyclin D1, cyclin E, and cyclin‐dependent kinase 2) and reduced p53 and p21, which enhanced hepatocyte viability. In contrast, estradiol both suppressed hepatocyte cell cycle markers, upregulated p53 and reduced viability of hepatocytes and HCC cells. Conclusions: Testosterone is the positive regulator of hepatocyte cell cycle via cyclin E, while estradiol plays a negative role by effects of p53 and p21. Together, both sex hormones determine the male predominance of gender differences in hepatocarcinogenesis.